Not another love song - Soto, Julie, 1988- (Forever, 2024)
"Two string players fight their attraction for each other as they compete for center stage in this spicy and emotional romance. Gwen Jackson and Xander Thorne are both musical prodigies, but each has had very different paths to success. Xander was born into classical music royalty, while Gwen had a natural ear for music that was nurtured by a kind shop owner. After Gwen performs at his friend's wedding, she's mortified when she realizes Xander has no clue who she is - despite having worked together for a year at the Pops Orchestra. But she's more furious that he arrogantly critiques her performance. When Gwen is offered the role of First Chair of the orchestra, something Xander had secretly coveted for years, their existing hostility goes up a notch. But their respect for each other's music is undeniable, and their onstage chemistry off the scale. As they begin to explore their feelings for one another, suddenly they're box office dynamite and the fragile romance that's growing between them is in danger of being crushed beneath a publicity stunt..."--